Social forestry business group financing strategy in Wanagiri Village, Sukasada District, Buleleng Regency, Bali Province - Musyaffa, Muhammad Elfaza Faishal; Boer, Rizaldi; Anggraeni, Lukytawati (International Journal Labs, 2025)
Social forestry is a flagship program to preserve forests while improving the welfare of communities around forest areas. This program faces several problems and challenges, one of which is the problem of financing social forestry business groups. The purpose of this study is to analyze alternative financing strategies for social forestry business groups. This study uses an in-depth interview method with the public and experts and the results are analyzed using descriptive analysis, SWOT and QSPM. Interviews with the community found that the financing of social forestry business groups is still minimal, this is due to several factors, including access to financing, government support, human resource capacity, and institutions, so alternative strategies are needed to increase the financing potential of social forestry business groups. Alternative strategies based on SWOT and QSPM analysis include actively looking for alternative sources of financing, increasing human resource capacity, evaluating the improvement of management of social forestry business groups, managing the environment sustainably, utilizing social forestry assistance facilities, conducting active communication with related institutions, and participation in collaboration between the community, government, and the private sector in the development of social forestry business groups.